Dark current analysis of InasSb-based hetero-p-i-n mid-infrared photodiode - Suo, Fei (2021)
We comprehensively study the characteristics of dark current for a p-i-n heterostructure photodiode. To reduce the dark current, a wide-bandgap layer (AlGaSb) and thin quaternary layers (AlInAsSb) are inserted in the heterostructure for blocking the dark carrier diffusion and limiting type-II transition at interface, respectively. The activation energy derived from measurement results indicates the positive (negative) correlation between the dominant dark current density and voltage bias (temperature). Whatever the voltage bias (temperature), this relationship always exists, indicating the high stability and reliability of our devices. Indeed, the measures taken for reducing dark current are confirmed to be effective as the dark current density for this photodiode is limited to a lower level. For the typical square mesa with 350 μm side length, at the bias of -0.4 V, the dark current density is 1.78 A/cm2 for T=293 K, and reduces to 0.4 A/cm2 for T=77 K, where the room-temperature value is lower than or comparable with that of the state-of-the-art mid-infrared photodetectors. A room-temperature detectivity of 8.3 × 108 cm · Hz1/2/W with a cut-off wavelength of 4 μm is demonstrated.